CHD5 is required for neurogenesis and has a dual role in facilitating gene expression and polycomb gene repression. - FARRAR, JANE (My University, 2013)
The chromatin remodeler CHD5 is expressed in neural tissue and is frequently deleted in aggressive neuroblastoma. Very little is known about the function of CHD5 in the nervous system or its mechanism of action. Here we report that depletion of Chd5 in the developing neocortex blocks neuronal differentiation and leads to an accumulation of undifferentiated progenitors. CHD5 binds a large cohort of genes and is required for facilitating the activation of neuronal genes. It also binds a cohort of Polycomb targets and is required for the maintenance of H3K27me3 on these genes. Interestingly, the chromodomains of CHD5 directly bind H3K27me3 and are required for neuronal differentiation. In the absence of CHD5, a subgroup of Polycomb-repressed genes becomes aberrantly expressed. These findings provide insights into the regulatory role of CHD5 during neurogenesis and suggest how inactivation of this candidate tumor suppressor might contribute to neuroblastoma.
PUBLISHED
Keywords: Genetics